74 OPVs, 70 elite inbred lines, and 200 hybrids shared in 2021 with national partners in West Africa for testing, adaptation, and release - CGIAR Research Program on Maize (2021)
Each year, national partners test CGIAR germplasm/material and select promising lines for further testing or national release trials.